CAMELLIA TRIAL: COMPARISON IN THERAPIES BASED ON CARVEDILOL AND METOPROLOL IN HYPERTENSIVE PATIENTS WITH OVERWEIGHT AND OBESITY - S. Y. Martsevich; N. P. Kutishenko (Рациональная фармакотерапия в кардиологии)
Therapy of arterial hypertension in patients with overweight and obesity has peculiarities. Reasons for comparable study of efficacy and safety of therapies based on β-blockers (carvedilol and metoprolol) in this type of patients are presented. Study aims and design, efficacy and safety criteria are described.